ANALISIS KEARIFAN LOKAL NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL SHIRAZY DAN RENCANA PELAKSANAAN PEMBELAJARANNYA DI KELAS XII SMA - Cahyani, Murni; Kadaryati, Kadaryati; Bagiya, Bagiya (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2019)
This research aims to describe: (1) intrinsic elements; (2) local wisdom contained in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy; (3) the plan to implement the learning of Bening Edged Bening novel by Habiburrahman El Shirazy in class XII of SMA. This research is a qualitative descriptive study. The results of this study concluded that (1) the intrinsic elements of the Bidadari Bering Bening novel, namely (a) themes: the major themes of the story of a woman's struggle in sustaining life, minor themes include, matchmaking, self-esteem, romance; (b) figures and characterizations: the main characters, namely Ayna and Gus Afif. Ayna is intelligent, assertive, patient and loyal, Gus Afif is intelligent, shy, responsible, humble, and independent; (c) flow: forward, (d) setting: setting, including Kanzul Ulum Islamic Boarding School, Lombok and Bait Ibni Sabil; time settings include morning, afternoon, evening and night; socio-cultural background including Javanese socio-cultural background); (e) point of view: the point of view of the all-knowing third person; (f) mandate: never put down others, never give up, and always be patient in the face of life's trials; (2) Local wisdoms in the Bidadari Bering Bening novel include (a) languages: Javanese, (b) knowledge systems: natural surroundings, natural flora, natural flora, and the characteristics and behavior of humans, (c) social organizations: systems kinship, (d) equipment of human life: food and shelter and housing, (e) livelihood system: merchants, (f) religious system: religious rituals and teachers / religious leaders, (g) arts: shadow puppets; (3) The plan for implementing novel text learning in class XII SMA based on the 2013 curriculum is contained in the basic competence 3.9 analyzing the contents of the novel and the language of the novel. The method used is a scientific-based Inquiry Learning method. Keywords: Clear-eyed Angels, intrinsic elements, local wisdom.